2012
DOI: 10.1016/j.tecto.2012.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Stress field of Italy — Mean stress orientation at different depths and wave-length of the stress pattern

Abstract: We have studied the stress pattern of Italy using a dataset with 590 data records from the World Stress Map database release 2008 and 106 new data records to test the hypothesis the mean orientation of maximum horizontal stress is different at different depth sections. For this, we split the dataset into a shallow (0-6 km) and a deep (6-40 km) depth section. For the data analysis we used a new statistical tool that calculates the mean orientation on a 0.2° grid. The tool takes into account the distance to each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 93 publications
7
40
0
Order By: Relevance
“…(d) Focal mechanism computed by INGV (http://cnt.rm.ingv.it/data id//4004047121/map dmt review.pdf) for the MW = 3.4, August 9, 2014 event. Seismic stations (triangles) are listed in Table 1. the other hand, the 2013 Marche offshore earthquakes (Mazzoli et al, 2014) confirmed a more complex tectonic behaviour of the Adriatic sector of the outer northern Apennines already suggested by Macchiavelli et al (2012) and Pierdominici and Heidbach (2012). There, focal mechanisms for events preceding the 2013 earthquakes were characterized by a wide range of orientation of P and T axes, and included thrust, strike-slip and extensional fault plane solutions (e.g.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…(d) Focal mechanism computed by INGV (http://cnt.rm.ingv.it/data id//4004047121/map dmt review.pdf) for the MW = 3.4, August 9, 2014 event. Seismic stations (triangles) are listed in Table 1. the other hand, the 2013 Marche offshore earthquakes (Mazzoli et al, 2014) confirmed a more complex tectonic behaviour of the Adriatic sector of the outer northern Apennines already suggested by Macchiavelli et al (2012) and Pierdominici and Heidbach (2012). There, focal mechanisms for events preceding the 2013 earthquakes were characterized by a wide range of orientation of P and T axes, and included thrust, strike-slip and extensional fault plane solutions (e.g.…”
Section: Introductionsupporting
confidence: 67%
“…On the other hand, the occurrence of NE-SW horizontal compression is clearly recorded by the 2013 Marche offshore earthquakes), suggesting that the complex, inherited fault structure characterizing the investigated area (Coward et al, 1999) may trigger significant local variations of the stress field resolved by seismological analysis (see also Macchiavelli et al, 2012;Pierdominici and Heidbach, 2012). This is consistent with the results obtained by Petricca et al (2013), who showed that a large variability of the stress field in this area results from a combination of first-order controls, due to plate tectonics (involving NNW-SSE convergence between the African and the Euroasian plates, occurring at a rate of 10 mm/year; Argus et al, 1989;Mazzoli and Helman, 1994) and mantle interaction, with second-and third-order sources including crustal structure, inherited Mesozoic features and present-day topography.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in an average data density of 0.21 data records per 100 km 2 , which is the typical claim size for exploration. In general, the orientation of the stress field does not change with depth in the upper crust Pierdominici and Heidbach, 2012;. Laterally the stress field in the Alpine Molasse rotates only gently anticlockwise from east to west .…”
Section: Introductionmentioning
confidence: 84%
“…Active normal faults along the crest of the Apennines are sub-parallel to the NW-SE striking mountain range and are controlled by the current large-scale, NE-SW trending extensional regime (for a summary: Basili et al, 2008;Devoti et al, 2008Devoti et al, , 2011DISS Working Group, 2010;Petricca et al, 2013;Pierdominici and Heidbach, 2012). The area among the southern Abruzzi, northern Campania, southeastern Lazio and southwestern Molise regions is the border between the central and southern Apennines and encompasses a large section of the OrtonaRoccamonfina Line, a regional structure striking NNE-SSW discussed by numerous authors (Fig.…”
Section: Introductionmentioning
confidence: 99%